Quinic acid: a potential antibiofilm agent against clinical resistant Pseudomonas aeruginosa - Lan Lu; Yuting Zhao; Guojuan Yi; Mingxing Li; Li Liao; Chen Yang; Chihin Cho; Bin Zhang; Jie Zhu; Kun Zou; Qiang Cheng (BMC, 2021)
Abstract Background The biofilm state of pathogens facilitates antimicrobial resistance which makes difficult-to-treat infections. In this regard, it has been found that the compounds screened from plant extracts represent one category of the most promising antibiofilm agents. However, the antibiofilm activities and the active ingredients of plant extracts remain largely unexplored. In this background, the study is (1) to screen out the plant extracts with antibiofilm ability against Pseudomonas aeruginosa, and (2) to identify the active ingredients in the plant extracts and elucidate the underlying mechanism of the antibiofilm activities. Methods Micro-broth dilution method, in vitro biofilm model, LC-MS/MS analysis and P. aeruginosa-mouse infection model were adopted to assess the antibiofilm activity. GC-MS analysis was performed to detect the active ingredients in plasma. RNA-Seq, GO analysis, KEGG analysis and RT-qPCR were adopted to elucidate the underlying mechanism of antibiofilm activities against P. aeruginosa. Results Lonicerae Japonicae Flos (LJF) among 13 plants could exert significant inhibitory effects on bacterial biofilm formation, mobility and toxin release in vitro, and it could exert antibiofilm effect in vivo too. Moreover, quinic acid, as one metabolite of chlorogenic acid, was found as an active ingredient in LJF against the biofilm of P. aeruginosa. The active ingredient significantly inhibited EPS secretion in biofilm formation and maturity and could achieve synergistic antibiofilm effect with levofloxacin. It reduced the biofilm formation by regulating core targets in quorum sensing system. In GO process, it was found that the core targets were significantly enriched in multiple biological processes involving locomotion, chemotaxis and motility mediated by flagellum/cilium, which was related to KEGG pathways such as bacterial chemotaxis, oxidative phosphorylation, ribosome, biofilm formation, cyanoamino acid metabolism and quorum sensing. Finally, the binding of quinic acid with core targets rhlA, rhlR and rhlB were validated by molecular docking and RT-qPCR. Conclusions In summary, the study verified the in vitro and in vivo antibiofilm effects of LJF against P. aeruginosa and elucidated the active ingredients in LJF and its conceivable pharmacological mechanism, indicating that quinic acid could have the potential of an antibiofilm agent against P. aeruginosa and related infections. Graphic abstract